Protective effects of resveratrol on the pharmacokinetics of tofacitinib in rats with cisplatin-induced acute renal failure - 정다운 (The Graduate School, Ajou University, 2024)
Tofacitinib, a JAK inhibitor commonly used to treat rheumatoid arthritis (RA), may result in renal involvement in RA patients due to chronic inflammation and drug toxicity. Tofacitinib undergoes 70% metabolism in the liver and 30% excretion via the kidneys. The area under the curve (AUC) of tofacitinib could elevate with the severity of renal disease, potentially leading to drug toxicity. Resveratrol, a natural polyphenolic substance in red grapes and wine, acts as a SIRT1 activator and antioxidant. It plays a role in preventing renal injury by reducing oxidative stress, inhibiting inflammation, and decreasing p53 acetylation, apoptosis, and cytotoxicity. This study investigated the pharmacokinetic changes of tofacitinib when administered with resveratrol in a rat model of cisplatin-induced acute renal failure (ARF). In vitro studies indicated a reduced expression of CYP3A1/2 and CYP2C11 in hepatic microsomes and decreased enzyme activity in hepatic and intestinal microsomes within the ARF group. Pharmacokinetic analysis revealed decreased clearance (CL), renal clearance (CLR), and non-renal clearance (CLNR). The renal injury observed in the ARF group led to diminished metabolism and excretion of tofacitinib, subsequently resulting in elevated plasma concentrations. In comparison to the CON group, intravenous and oral administration in the ARF group showed induction in the AUC, with an increase of 190% and 103%, respectively. Preliminary results indicate decreased Blood Urea Nitrogen (BUN) and Serum Creatinine (SCR), along with an increased Creatinine Clearance (CLCR) in rats experiencing acute renal failure pretreated with resveratrol (AR). In vitro studies indicated an increased expression of CYP3A1/2 and CYP2C11 in hepatic microsomes, along with increased enzyme activity in hepatic and intestinal microsomes in the AR group. Pharmacokinetic analysis revealed that CL, CLR, and CLNR were restored in the AR group. Resveratrol pretreatment mitigated renal dysfunction, consequently restoring the metabolism and excretion of tofacitinib. This resulted in lower plasma concentrations of tofacitinib and subsequently decreased AUC. In comparison to the ARF group, the AUC in the AR group decreased by 49.2% for intravenous administration and by 38.2% for oral administration.
학위논문(석사)--바이오헬스규제과학과,2024. 2
Keywords: acute renal failure; pharmacokinetics; renal protective effect; resveratrol; tofacitinib